Unsticking Litigation Science - Beerdsen, Edith (Science and Technology Law Review, 2025)
Litigation science is increasingly out of step with academic, knowledge-producing science. Research practices in the social sciences have changed dramatically in the past fifteen years, in response to a knowledge crisis now popularly known as the “Replication Crisis.” The Replication Crisis caused an evolution in scientists’ understanding of what it takes to create reliable science and radically altered the way social science is conducted today. Central to these reforms is a focus on the elimination of “Analytical Flexibility”—the flexibility a researcher has to alter a research protocol along the way—in recognition of the fact that Analytical Flexibility has a propensity to lead to research results that are not only unreliable but also unreliable in undetectable ways. The Replication Crisis represents a paradigm shift that has not yet been recognized by the legal community. In this symposium paper, I describe how litigation science and academic science are currently on divergent paths, and argue that it is critical for courts and litigators to start engaging with recent progress in research methodology. In the academic sciences, modern research practices such as preregistration are increasingly becoming routine and expected by journals, peer reviewers, and funders. Meanwhile, testifying experts retained in connection with litigation essentially proceed as they always have, and disclosure requirements have remained unchanged. Litigation science is at risk of becoming a quaint, historically shaped discipline that bears scant relationship to its academic, knowledge-producing cousin. If we do not reform how litigation science is produced and presented, it will increasingly be seen as incapable of producing information that can usefully inform relevant issues in litigation.